KEMAMPUAN MANAJERIAL KEPALA SEKOLAH PADA TAMAN KANAK-KANAK - Fauziana, Aulia Oktavia; Yetri, Yetri; Fauzan, Ahmad; Dermawan, Oki (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to describe the managerial capabilities of kindergarten principals in improving the quality of early childhood education. The golden age of children, ranging from 0 to 6 years, is a critical period that shapes cognitive, socio-emotional, language, and motor skills development. Therefore, the success of early childhood education largely depends on the leadership quality of school principals as educational managers. This research used a library research method by analyzing relevant journals, scholarly articles, and books. The findings show that kindergarten principals with strong managerial skills effectively carry out management functions: planning, organizing, actuating, and controlling (POAC). Additionally, principals play multiple roles as educators, administrators, supervisors, leaders, innovators, and motivators. These roles significantly contribute to teacher performance and the overall quality of learning in the school. Previous studies confirm a positive and significant relationship between principals' managerial competencies and both teacher performance and student learning outcomes. Effective principals are able to create a positive school climate, implement participatory leadership strategies, and build synergy among teachers, parents, and external stakeholders. In conclusion, the improvement of early childhood education quality is strongly influenced by the managerial capacity of school principals, which includes a range of strategic roles in educational management. Therefore, ongoing training and capacity building for principals are essential efforts in developing the overall quality of early childhood education institutions. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan kemampuan manajerial kepala sekolah dalam meningkatkan mutu pendidikan di Taman Kanak-Kanak. Masa emas anak usia 0–6 tahun merupakan periode krusial yang menentukan arah perkembangan kognitif, sosial emosional, bahasa, serta fisik motorik anak. Oleh karena itu, keberhasilan pendidikan anak usia dini sangat bergantung pada kualitas kepemimpinan kepala sekolah sebagai manajer lembaga pendidikan. Penelitian ini menggunakan metode studi pustaka (library research), yang dilakukan dengan menelaah berbagai jurnal, artikel ilmiah, dan buku yang relevan. Hasil kajian menunjukkan bahwa kepala sekolah TK yang memiliki kemampuan manajerial tinggi cenderung berhasil menjalankan fungsi manajemen: perencanaan, pengorganisasian, pelaksanaan, dan pengawasan (POAC). Selain itu, kepala sekolah juga berperan sebagai guru, administrator, pengawas, pemimpin, inovator, dan motivator. Peran-peran ini terbukti mendorong peningkatan kinerja guru dan mutu pembelajaran di sekolah. Studi-studi terdahulu mengonfirmasi adanya hubungan positif dan signifikan antara kompetensi manajerial kepala sekolah dengan kinerja guru serta capaian pembelajaran peserta didik. Kepala sekolah yang efektif mampu menciptakan iklim sekolah yang kondusif, menerapkan strategi kepemimpinan partisipatif, serta membangun sinergi antara guru, orang tua, dan pihak luar. Kesimpulannya, peningkatan mutu pendidikan anak usia dini sangat dipengaruhi oleh kemampuan manajerial kepala sekolah yang mencakup berbagai peran strategis dalam manajemen pendidikan. Oleh karena itu, pelatihan dan penguatan kapasitas kepala sekolah menjadi langkah penting dalam pengembangan kualitas PAUD secara menyeluruh.